Antioxidant Activity, Antibacterial Activity and Chemical Composition of Essential Oil of Artemisia vulgaris L. Leaves from Northeast India. Issue 2 (4th March 2019) - Munda, Sunita; Pandey, Sudin Kumar; Dutta, Sukriti; Baruah, Joyashree; Lal, Mohan
Abstract: The present work has been aimed to investigate the chemical composition of the essential oil of Artemisia vulgaris L. leaves by gas chromatography followed by mass spectrometry method (GC/MS), antioxidant activity by DPPH radical scavenging activity, reducing power, total phenolic content, total flavanoid content compared to ascorbic acid for phenols and quercetin for flavonoids. The essential oil was further evaluated for antibacterial activity against five human pathogenic strains: Bacillus subtilis, Bacillus cereus, Staphylococcus aureus, Salmonella typhimurium and Escherichia coli compared to antibiotic ciprofloxacin. The GC/MS analysis of the essential oil of Artemisia vulgaris leaves showed the presence of 38 compounds out of which 1, 8-cineole, camphor, isopulegol, borneol, β-caryophyllene, chavicol and myrtenol are the major compounds. The IC50 value of the DPPH radical scavenging activity and reducing power of the essential oil was 2.745 μg mL -1 and 2.845 μg mL -1 respectively as compared to ascorbic acid with IC50 value of 10.83 μg mL -1 and 21.15 μg mL -1 . The total phenolic content and total flavanoids content of the plant essential oil were found to be 6.2 mg mL -1 and 220 mg mL -1 respectively. The essential oil showed antibacterial activity against all the selected strains with lowest MIC value of 5 μg mL -1 and 20 μg mL -1 shown by Bacillus cereus and Staphylococcus aureus and MBC value of 80 μg mL -1 and 100 μg mL -1 shown by Bacillus cereus and Bacillus subtilis .